Effects of validation and invalidation on running performance of athletes - Barban, Marilia; Leonardi, Jan Luiz (Perspectivas em Análise do Comportamento, 2018)
Validation and invalidation influence emotion regulation, powering or hindering the quality of relationships, adaptation in stressful activities and tolerance to pain. Considering that in the area of sport there is not always a concern with the athlete’s feelings, during training as well at a competition, this research had as objectives to evaluate the effects of validation and invalidation on (1) the athlete’s performance; (2) the acceptance to perform an extra training; (3) the perception of the training difficulty, and (4) the positive and negative emotions. An experimental study was carried out in which 16 athletes of different modalities performed 100m shots and answered questions and questionnaires about their experience, receiving validation or invalidation from the researcher. The results showed that invalidation resulted in higher scores of negative affects and to the perception of the training difficulty, greater refusal to perform additional training and lower performance. Such data can be used to guide coaches and athletes to adopt less invalidating postures and thus favor more effective training and better results in performance.